Reseña de Bybee, J. and S. Fleischman (1995), Modality in Grammar and Discourse, (TypologicalStudies in Language 32), Amsterdam/Philadelphia, John Benjamins Publishing Company. - Berbeira Gardón, José Luis (Pragmalingüística, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Se trata de una reseña de Bybee, J. and S. Fleischman (1995), Modality in Grammar and Discourse, (TypologicalStudies in Language 32), Amsterdam/Philadelphia, John Benjamins Publishing Company.